Estimation of the productivity of rice samples under severe field drought - P. I. Kostylev; A. V. Aksenov; E. V. Krasnova (Зерновое хозяйство России)
Drought is one of the most important factors hindering the cultivation of rice, resulting in large yield losses, and limiting productivity growth. The purpose of the current study was to determine the drought resistance of rice varieties and samples of various origins under conditions of periodic irrigation with periods of prolonged soil aridity and high air temperature, to identify drought-resistant plants for the selection of upland varieties. There have been studied 68 varieties and samples of upland rice when grown on irrigated and flooded areas (Proletarsk, Rostov region). There has been established that varieties and samples under drought conditions and sufficient water supply formed different grain productivity, which in 2020–2021 with a lack of water amounted to 63.7 % of the norm, and in 2022 to 30.1 %. There has been found that the correlation of rice productivity under dry conditions with that under full moisture supply was weak negative (r = –0.22±0.12), and with the drought resistance index (DRI) it was high positive (r = 0.95±0.04). The values of quantitative traits under drought conditions have changed significantly in comparison with the control. Such traits as plant height (95.7 %), panicle length (73.1%), panicle density (58.7 %), number of harvested plants per 1 m2 (87.3 %), plant weight (42.3 %), panicle weight (25.1 %), total number of spikelets (54.5 %) and grains per panicle (32.4 %), 1000-grain weight (70.4 %) have decreased. Such traits as number of productive stems per 1 m2 (115.2 %), tilling capacity (126.1 %), the number of empty spikelets per panicle (205.1 %) and the percentage of empty grains (339.1 %) have increased. There have been identified such 9 varieties and samples with DRI from 51.1 to 93.7 % as ‘Kontro’, ‘An-Yun-Ho’, ‘Chan-Chun-Man’, ‘Hong-Mo’, ‘8323’, ‘8338’, ‘8337’, ‘ZULK 8’, ‘ZULK 9’, which formed maximum productivity in dry conditions (3.95–5.51 t/ha).